Investigating Fatigue of Three-Dimensional Flow Phantom Model of the Carotid Artery of Preterm Infants - Pereira, Sujith; Reeves, Jonathan; Birch, Malcolm; Ali, Ahmed S.; Sinha, Ajay K.; Kempley, Stephen T. (British Journal of Healthcare and Medical Research, 2022)
This study aimed to examine phantom fatigue and perform flow volume measurements with Doppler ultrasound using 3D printed flow phantom models of carotid artery in preterm infants. 3D printed Doppler flow phantom model with three different vessel diameters; 0.158 cm, 0.196 cm and 0.244 cm and varying characteristics that were 18 to 24 months old were used for these experiments. Leading edge to centre was used to measure vessel diameter. Two observers performed flow volume measurements using continuous and pulsatile flow. Agreement between observers was examined using Bland-Altman plots. 36 measurements were performed. 9 (50%) measurements were performed using continuous flow. Pulsatile flow measurements were performed using physiological rates. Bland-Altman analysis for continuous flow diameter measurements for observer 1 and 2 were -0.004 (95%LOA -0.012 to 0.005) cm and -0.006 (-0.022 to 0.010) cm. Bias for pulsatile flow diameter measurements were smaller both observers. Bias for continuous flow measurements for observer 1 and 2 were 0.382 (95%LOA -5.306 to 6.070) ml/min and 3.516 (-4.030 to 11.06) ml/min respectively. Bias was smaller for pulsatile flow measurements. Inter observer reliability was excellent for majority of measurements. The coefficient of variation for all diameter measurements for both observers ranged from 0.29% to 4.47%. 3D printed flow phantom that were nearly 2 years old maintained their structural integrity and produced ultrasonographic images similar to when they were first used. Validity and reliability studies between observers showed acceptable results. Researchers and clinicians can use this model for further training and simulation in the long term.